2014
DOI: 10.1080/00927872.2013.765006
|View full text |Cite
|
Sign up to set email alerts
|

Zigzag Theorem for Partially Ordered Monoids

Abstract: While investigating the connection of absolute flatness of partially ordered monoids (briefly pomonoids) with their amalgamation, the author recently posed the question as to whether it was possible to formulate some ordered analogue of Isbell's zigzag theorem. Proving such a theorem is the primary aim of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In fact these transformations come from those given in [2] p. 286; in [6] pp. 2573-2574 we observed that for pomonoids it suffices to consider rather the set F = {Ea, Eb, M, S, I a, I b, i} of above transformations.…”
Section: Amalgamated Coproductsmentioning
confidence: 95%
See 4 more Smart Citations
“…In fact these transformations come from those given in [2] p. 286; in [6] pp. 2573-2574 we observed that for pomonoids it suffices to consider rather the set F = {Ea, Eb, M, S, I a, I b, i} of above transformations.…”
Section: Amalgamated Coproductsmentioning
confidence: 95%
“…We shall also revisit a zigzag theorem for pomonoids, proved in [6]. We begin by recalling dominions.…”
Section: Claim 1 If F : S −→ T Is An Epimorphism In the Category Of Pmentioning
confidence: 99%
See 3 more Smart Citations